Strategies for Internalizing Religious Character Values ThroughDigital Storytelling at Madrasah Ibtidaiah Hidayatus Shibyan - Erna Nur Komariah; Anas Azhar Nasim (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
The digital era presents a disruptive challenge for character education, where conventional learning methods often fail to resonate with the interests of the digital native generation and trigger the phenomenon of student moral degradation that is increasingly rampant. Therefore, innovative pedagogical strategies are needed that are able to bridge these gaps by integrating religious values through visual-narrative media that are relevant to the student ecosystem. This study aims to: 1) Analyze the implementation strategy of digital storytelling in PAI learning. 2) Identify the Content of Religious Character Values Integrated in PAI Learning. 3) Evaluate the Implications of Media Use on Student Responses and Behaviors. This study uses a descriptive qualitative approach with a case study design at Madrasah Ibtidaiah Hidayatus Shibyan, where data is collected through in-depth interviews, participant observations, and documentation and analyzed using the Miles, Huberman, and Saldana interactive models. The results of the study show that: 1) The implementation strategy is carried out systematically through careful narrative content planning, curriculum integration, and school culture habituation supported by the active role of teachers as facilitators; 2) The content of the main character's values that have been successfully internalized includes aspects of piety, honesty, politeness, helping, and love for the Apostle; and 3) The use of digital storytelling has significant implications in increasing students' cognitive attention, deepening value appreciation, and encouraging the transformation of affective behavior into concrete moral principles in daily life.